6
$\begingroup$

Here I go :

$3 + 5 + 6 = 15 \ 18 \ 72$
$5+ 5 + 6 = 25 \ 30 \ 94$
$5 + 6 + 7 = 30 \ 35 \ 85$
$5 + 5 + 3 = 25 \ 15 \ 73$
$9 + 4 + 7 = 36 \ 63 \ ? $

Replace ? with appropriate number

$\endgroup$
  • $\begingroup$ Do you mean digit or number? $\endgroup$ – M Oehm Jul 14 '16 at 7:06
19
$\begingroup$

Answer is

$29$

Explanation:

The formula is:
$a + b + c = a*b \quad a*c\quad ((a*b) + (a*c)) - c$

Take the example of the first row
$3 + 5 + 6 = 15$ $18$ $72$
Let $a = 3, b = 5 , c = 6$

$((3*5) + (3*6)) - 6 \Rightarrow (15 + 18) - 6 \Rightarrow 33 - 6 \Rightarrow 27$
Reverse of $27$ is $72$

In the same way for the last row
For $9 + 4 + 7 = 36$ $63$ $?$

$((9*4) + (9*7)) - 7 \Rightarrow (36 + 63) - 7 \Rightarrow 99 - 7 \Rightarrow 92$
reverse of $92$ is $29$

$\endgroup$
0
$\begingroup$

for the missing value

173.32

because

for the third column I get $$26.4 * a - 0.6*b + 7c -3.08ab$$

$\endgroup$
  • 3
    $\begingroup$ I thinnk you are unnecessarily making it more difficult. $\endgroup$ – Hisenberg Jul 15 '16 at 2:36
  • 1
    $\begingroup$ simpler or more complex is in the eye of the beholder. $\endgroup$ – Jasen Jul 15 '16 at 2:37

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.